Influence of Piper sarmentosum aqueous extract on the expression of osteocalcin in glucocorticoid-induced osteoporotic rats - Mohd Ramli, Elvy Suhana; Soelaiman, Ima Nirwana; Mohd Thani, Suryati; Mohd Nor, Nurul Huda; Mohamad Zainal, Nurul Hayati; Masrudin, Siti Saleha; Mohamad Asri, Siti Fadziyah (Universiti Putra Malaysia Press, 2023)
Secondary osteoporosis is mainly caused by prolong used of glucocorticoid treatment. The Piper sarmentosum leaf aqueous extract was found to exhibit bone formatting osteocalcin activity against Dexamethasone induced osteoporotic rats. Thirty-two Sprague-Dawley rats were divided equally into four groups - G1: Sham-operated control group given intramuscular (IM) olive oil as vehicle and normal saline orally as vehicle; G2: Adrenalectomized (Adrx) control group given IM dexamethasone (DEX) (120 μg/kg/day) and normal saline orally as vehicle; G3: Adrx group given IM DEX (120 μg/kg/day) and aqueous extract of Piper sarmentosum leaves (125 mg/kg/day) orally; and G4: Adrx group given IM DEX (120 μg/kg/day) and glycyrrhizic acid (GCA) (120 mg/kg/day) orally. Immunohistochemical method with gold labelling was used to label the osteocalcin protein. Silver brightener was used, sprinkled on gold with a size of 5 nm so that the resulting image can be seen more clearly using a light microscope. The osteocalcin protein was measured quantitatively based on nomenclature report of the ASBMR Histomorphometry Committee (American Society for Bone Mineral Research). The activity shown by immunohisto-gold expression and localization of osteocalcin was comparable with the reference, glycyrrhizic acid, a potent inhibitor of 11β-hydroxysteroid dehydrogenase enzyme in RANKL-OPG pathway. As a conclusion, Piper sarmentosum may one day be utilized as an alternate treatment for individuals receiving long-term glucocorticoid therapy to prevent osteoporosis, therefore osteoporotic fractures.